Struktur Komunitas Gastropoda pada Beberapa Spesies Mangrove di Ekosistem Mangrove Desa Pejarakan, Bali - Asmarani, Putu Gita; Indrawan, Gede Surya; Ernawati, Ni Made (Journal of Marine Research and Technology; Vol 7 No 2 (2024): OKTOBER 2024DO - 10.24843/JMRT.2024.v07.i02.p07, 2024)
Mangrove ecosystem is vegetation that grows in coastal areas and acts as a habitat for aquatic biota, including Gastropods c. Research of the structure communities of gastropods in several mangrove species in the mangrove ecosystem in Pejarakan Village was carried out in January 2024. This research aims to determine the species and diversity of gastropods and determine water parameters and substrate types. The research was conducted using the quadrant transect method with 45 points, 15 points each, in three mangrove vegetation zones. The results obtained showed that there were seven species of gastropods from 5 families. The families found were Cypraenidae, Ellobidae, Littorinidae, Muricidae, and Potamididae, with the highest abundance being Telescopium Telescopium at 2.93 and/m2. The gastropod diversity index ranged between 1.06 to 1.35, the evenness index ranged from 0.70 to 0.84, and no dominant species was found. The results of measuring water parameters showed an average pH temperature of 6.54, a temperature of 29.05 °C, and a salinity of 31.43. Meanwhile, the substrate type in the research area is dominated by muddy substrates.